Efecto de la temperatura y tiempo de remojo del arroz en cáscara para la obtención de arroz parbolizado - Zamora Sanchez, Elmer Yampier (2019)
In the present study was determined the effect of temperature and time of soaking of the rice in shell were determined, to obtain greater yield in whole polished grain in the process of the rice parboiled by hydrothermal treatment. For which it was used the central composite rotational design (CCRD) with 11 experiments with hydration temperatures between 70 ° C and 95 ° C, and hydration times between 90 and 120 min. After steeping, steam cooking was carried out at a pressure of 0.151 MPa and a temperature of 110 ° C for a time of 10 min and drying at a temperature of 40 ° C ± 1 ° C. As a result, it was obtained that both time and temperature affected the whole grain yield quadratically, since a minimum yield point was obtained. From this, the variations of both variables caused an increase in the whole polished grain yield. It was concluded that higher temperatures and hydration times result in higher yields of whole polished grain. For obtaining yields between 90% - 100%, it would be necessary to use hydration times between 110 and 115 min and hydration temperatures between 92 and 94 ° C.